KAJIAN ANALISIS KESESUAIAN POTENSI EKOWISATA DI OBJEK DANAU SOLE KECAMATAN AMARSEKARU KABUPATEN SERAM BAGIAN TIMUR - Supriyadi Kilbaren; Yosevita Th. Latupapua (JURNAL HUTAN PULAU-PULAU KECIL, 2017)
Lake Sole is a natural lake in East Seram Regency that has a unique nature and uniqueness in the color and taste of the water. This uniqueness makes more value on the lake when compared with the lakes in general. The uniqueness and naturalness that is owned, has not provided significant benefits to the local community and local PAD. Therefore, the purpose of this research is to know the potential of ecotourism attraction which is owned by Lake Sole, and the form of local community participation in supporting the development of ecotourism attraction product. The methods used in data collection are survey methods, interviews, and questionnaire distributions. The analysis used is quantitative descriptive analysis. The result of the research shows that Lake Sole has "high" conformity index value as ecotourism attraction product, but it needs involvement of stakeholders in supporting the development of tourism facilities and infrastructure that has been done by the community. Form of community participation that has been done to support tourism activities in Lake Sole in the form of selling food and beverages, owners of local transportation modes, homestays, and local guides.